Levantamiento geológico – estructural a escala 1:10000 de la zona Norte de la parroquia La Tingue perteneciente al cantón Olmedo, provincia de Loja. - Ojeda Carrión., Fabricio Xavier (2022)
The structural geological survey at a scale of 1:10 000, carried out in the Northern area of the La Tingue parish, covers an area of 25.74 km2, it is geographically located in the Southern Region of Ecuador, Loja province, Olmedo canton and has the following biophysical characteristics: predominance of very high mountainous and hilly reliefs, mostly with slopes in a range of 15° - 35° and 35° - 55°; that is to say, very inclined and steep respectively, it presents a detrital hydrographic network - subparallel and a predominance of herbaceous vegetation with climates of megathermal character. The characterization of the local geology of the work area was carried out through the outcrop mapping method, in which 5 lithological units were determined with the following particularities: the Celica Unit comprises an area of 2.28 km2, it is constituted as the basement of the study area and is made up of volcanic and volcanoclastic materials: porphyritic andesites, volcanic tuffs and basaltic andesites. The Chaguarpamba Unit has an area of 5.73 km2 and is made up of a sequence of volcanoclastic materials: sandy tuffs, volcanic agglomerates and tuffaceous siltstones that overlie the sandy tuffs mentioned above. The Ciano Unit has an area of 1.01 km2 and is made up of the following clastic sedimentary materials: shale, sandstone, and sandstone with volcanic lithics underlying the shale. The Zambi Unit is characterized by representing a larger area of territory, covers an area of 16.30 km2 and is made up of siltstones and metalutites. On the other hand, the volcanic and volcanoclastic sequences are intruded by moderately weathered granodioritic rocks. The geological structure of the Northern zone of La Tingue parish presents a system of faults mainly located to the South and North-East, in a preferential direction NW - SE and NE - SW, outcropping mainly in ravines and lithological contacts; it is made up of five inferred faults, two inferred dextral faults, one observed reverse fault, and one observed sinistral fault. In addition, rock masses with fractures and without block displacement were visualized: tectonic and inclined joints with a preferential dip direction to the NW; finally, plastic deformations were evidenced, giving rise to a syncline fold. Keywords: geological survey, structural geology, outcrop mapping, La Tingue Norte, geological-structural map.